Conductivity of SbxSey films grown by CMBD from Sb and Se precursors for use in solar cells. (December 2021) - Razykov, T.M.; Bosio, A.; Ergahsev, B.A.; Isakov, D.; Khurramov, R.; Kouchkarov, K.M.; Romeo, A.; Romeo, N.; Tivanov, M.S.
Highlights: The conductivity of Sbx Sey films was studied as a function of the vapor phase mixture of Sb and Se. The conductivity was varied in the wide range of 10 −5 –10 2 (Ohm × cm) −1 . The obtained results were explained by the formation of intrinsic point defects. Abstract: Antimony selenide (Sb2 Se3 ) has been developed as attractive, non-toxic and earth-abundant solar absorber candidate among the thin-film photovoltaic devices. The growth of Sbx Sey thin films, by atmospheric pressure chemical molecular beam deposition (CMBD) method, from separate Sb and Se precursors has been reported. The conductivity of the films was investigated as a function of the vapor phase mixture of Sb and Se. By the precise control of the Sb/Se ratio we succeeded in obtaining stoichiometric Sb2 Se3 films. It is also found out that we can control the conductivity by deliberately introducing the deviation from the stoichiometry. The conductivity was varied in the wide range of 10 −5  ÷ 10 2 (Ohm × cm) −1 and samples had p- and n-type conductivity depending on Sb/Se ratio. The obtained results were explained by the formation of intrinsic point defects.